2016
DOI: 10.1088/1367-2630/18/4/043026
|View full text |Cite
|
Sign up to set email alerts
|

Creating analogs of thermal distributions from diabatic excitations in ion-trap-based quantum simulation

Abstract: One broad goal of quantum simulation is to start a simple quantum system in its ground state and slowly evolve the Hamiltonian to a complex one, maintaining the ground state throughout the evolution (called adiabatic state preparation). This provides a natural setting to create a highly entangled and correlated quantum state if the final Hamiltonian supports such a ground state. In iontrap-based quantum simulations, coherence times are too short to allow for such ground-state evolution for large chains, becaus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Another interesting question is the following: In cases where the pure state |ψ 0 represents a thermal distribution well, in the sense that the coefficients |C n | 2 are nearly proportional to the Boltzmann factor [22], then does the pure state retarded spin-spin Green's function represent the thermally averaged retarded Green's function well? One might expect this to be true, because the diagonal elements in the summation will closely resemble the trace employed in the calculation of the thermal Green's functions, and the off diagonal elements should become small as the system size becomes large due to cancellations from the complex phases.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting question is the following: In cases where the pure state |ψ 0 represents a thermal distribution well, in the sense that the coefficients |C n | 2 are nearly proportional to the Boltzmann factor [22], then does the pure state retarded spin-spin Green's function represent the thermally averaged retarded Green's function well? One might expect this to be true, because the diagonal elements in the summation will closely resemble the trace employed in the calculation of the thermal Green's functions, and the off diagonal elements should become small as the system size becomes large due to cancellations from the complex phases.…”
Section: Discussionmentioning
confidence: 99%
“…But in general, our results also show that when a system has significant frustration, no technique can maintain a high probability in the ground state, and so it is more useful to consider working with the diabatic distribution of excited states that ensues. In some cases, these distributions can closely mimic thermal distributions [14], but this does not often occur for frustrated spin systems. We examined the distributions of excited states for some of the different systems studied here, and found that the locally adiabatic distribution was not too thermal, but did have a preponderance of the excitations towards the lower energy part of the spectrum.…”
Section: Fig 4 (Color Online)mentioning
confidence: 99%
“…In the second category, we already mentioned experimental [4,5,7] and theoretical [6] methods to produce or measure specific excitations. It also is possible, in some cases, for the diabatic excitations to resemble an equilibrium thermal state, especially for ferromagnetic systems [14].…”
mentioning
confidence: 99%
“…5, we show the numerical evaluation of the G . Note that this wavefunction is not a thermal state, but it is a linear combination of the eigenstates with the amplitudes of each state chosen to have the same probability as in a thermal state [19]. Dots indicate measurements of the transverse-field Ising model Green's function at the particular times which correspond to the simulation of the XY model Green's function.…”
Section: E Green's Functionmentioning
confidence: 99%